First‐in‐human study assessing safety, tolerability and pharmacokinetics of BI 409306, a selective phosphodiesterase 9A inhibitor, in healthy males. (22nd August 2016) - Moschetti, Viktoria; Boland, Katja; Feifel, Ulrich; Hoch, Anja; Zimdahl‐Gelling, Heike; Sand, Michael
Abstract : Aims: The aim of the present study was to investigate the safety, tolerability, dose proportionality and relative bioavailability of tablet and oral solution formulations of BI 409306 in healthy male subjects, and to compare the safety and pharmacokinetics in subjects who were extensive metabolizers (EMs) or poor metabolizers (PMs) of cytochrome P450 (CYP)‐2C19. Methods: The present randomized, double‐blind, placebo‐controlled, single‐centre study evaluated single rising doses of BI 409306 (0.5–500 mg) administered as a tablet or oral solution to EMs or PMs. Results: Of 80 enrolled subjects (mean age 36.7 years), 79 (CYP2C19 EMs, 71; CYP2C19 PMs, eight) received treatment and completed the study. Adverse events (AEs) were mild to moderate in intensity. Overall, 17/71 (23.9%) EMs and 6/8 (75.0%) PMs experienced 28 and eight AEs, respectively, of which, 25 and seven AEs, respectively, were considered to be drug related. The most frequently reported AEs were nervous system and eye disorders; all occurred shortly (20–30 min) after administration and mostly resolved within 1–2 h. No serious AEs occurred. BI 409306 systemic absorption and elimination were rapid; peak plasma concentration (Cmax ) was reached <1 h after drug administration, and the half‐life ranged from 0.99 h to 2.71 h. Both the tablet and oral solution resulted in similar exposures. In PMs, at dose levels of 10 mg and 100 mg, Cmax was 2.2–2.3‐fold higher, and the area under the plasma concentration–time curve over the time interval 0 extrapolated to infinity was 4.1–5.0‐fold higher compared with EMs. Conclusions: In healthy male subjects, BI 409306 was generally safe and well tolerated, with rapid absorption and elimination. Systemic exposure was higher in CYP2C19 PMs than EMs at the same dose level.